Pick's Disease: A Clinical Analysis Regarding its Etiology - Hernando Rafael (2012)
Background: The clinical course of Pick´s disease (PD) is similar to that of Alzheimer´s disease (AD). Clinical cases: We present the clinical course and CT-scan findings in 3 patients (two sporadic cases and one familial case) diagnosed with PD. Results: The course of this disease was characterized by the following: 1) behavioral and personality changes; 2) progressive impairment of recent memory; 3) sex disturbances and /or appetite increase; 4) upper cortex dysfunction; 5) motor, sensorial and sphincter control worsening, and 6) posture and gait impairment, as well as prostration. Brain tomography studies demonstrated atherosclerosis at the supraclinoid segment of carotid arteries and its branches, and also moderate or severe atrophy in both prefrontal and anterior temporal lobes. Conclusions: These findings suggest that PD is also caused by progressive ischemia in the intra-parenchymal territory of the anterior perforating, anterior choroidal, and lenticulostriate arteries; due to atherosclerotic plaques located at the origin of these arterial branches.